ANALISIS KEUNTUNGAN USAHA PEMBESARAN IKAN NILAMERAH (Oreochromis sp.)(Studi Kasus di P4S Al-Mukhlis Desa Kiangroke Kecamatan Banjaran Kabupaten Bandung) - Kundratr; Kundrat; Lily Sumarti; Rimelke Rahmadia Febryane; Erfan; Haelan Azha (Program Studi Agroteknologi Faperta UNIBBA, 2025)
Tilapia is a widely cultivated freshwater fish species in Indonesia, with well-established cultivation technology and high production levels. Among the commonly farmed varieties are black tilapia and red tilapia. The market potential for tilapia remains significant, both domestically and internationally, especially in fillet form, with export destinations including the United States, Europe, the Middle East, and Hong Kong. This study aims to analyze the economic feasibility of red tilapia grow-out farming at P4S Al-Mukhlis by identifying (1) the total cost and revenue generated, (2) the profitability of the business, and (3) the break-even point (BEP) of the operation. The research was conducted from February to April 2023 at P4S Al-Mukhlis, Banjaran, using a quantitative descriptive approach with purposive sampling. Data collection was carried out through interviews, discussions, and field observations. The results showed that the total production cost amounted to Rp 11,076,027.75, while revenue reached Rp 17,745,000 from the production of 507 kg of red tilapia. The R/C ratio was 1.60, indicating a profit of Rp 0.60 for every Rp 1.00 invested, thus confirming the business’s profitability. The break-even point was achieved at a production volume of 214 kg, with a selling price of Rp 21,800 per kg, requiring a minimum revenue of Rp 7,472,400. These findings demonstrate that red tilapia grow-out farming at P4S Al-Mukhlis is economically viable and profitable.